Multidimensional Poverty Assessment of Internally Displaced Persons in Iraq - Noumedem Temgoua, Claudia; Sharma, Dhiraj; Wai-Poi, Matthew (World Bank, Washington, DC, 2020)
Decades of conflict have contributed to high flows of internal displacement in Iraq. The incidence of these flows on the welfare of internally displaced persons is not well understood. This paper attempts to fill this gap in the literature by investigating the link between internal displacement and multidimensional poverty, using one of the most comprehensive household surveys for poverty analysis in Iraq. The results show crucial differences between internally displaced and non-displaced households with respect to multidimensional poverty. Furthermore, instrumental variable regression analysis suggests that the relationship is causal, that is, the probabilities of multidimensional and monetary poverty are higher because of internal displacement.